2013
DOI: 10.5478/msl.2013.4.4.79
|View full text |Cite
|
Sign up to set email alerts
|

General Fragmentations of Alkaloids in Electrospray Ionization Tandem Mass Spectrometry

Abstract: Various types of alkaloids observed in several herbal medicines were analyzed by electrospray ionization tandem mass spectrometry in positive ion mode. In the present study, MS/MS spectralpatterns were investigated for eight-types of alkaloids (aporpine, protoberberine, tetrahydroprotoberberine, benzylisoquinoline, protopine, phthalide, morpine, and bisbenzylisoquinoline). For aporpine-and protoberberine-type alkaloids, main fragmentations occurred at substituted groups on rigid ring structures, not showing ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…Note: A, Aporphine; B, benzylisoquinoline; T, tetrahydroprotoberberine; O, others; d, Stévigny et al ., ; e, Schmidt et al ., ; f, Shim et al ., .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Note: A, Aporphine; B, benzylisoquinoline; T, tetrahydroprotoberberine; O, others; d, Stévigny et al ., ; e, Schmidt et al ., ; f, Shim et al ., .…”
Section: Resultsmentioning
confidence: 93%
“…An ion at m / z 178 was previously observed in the electron ionisation (EI) MS of tetrahydroprotoberberine alkaloids containing methoxyl and a hydroxyl groups at the ring A, such as scoulerine and caseamine (Chen and Maclean, ). In ESI‐MS experiments it was suggested that this diagnostic ion is formed via a RDA ring opening of the protonated molecule (Shim et al ., ) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetrahydroprotoberberines undergo fragmentation via cleavage of the C aromatic ring. For benzyltetrahydroisoquinoline or aporphine alkaloids, elimination of dimethylamine from ammonium group, followed by loss of small molecules, such as methane, methanol or carbon monoxide is observed .…”
Section: Introductionmentioning
confidence: 99%